2014
DOI: 10.3324/haematol.2014.107326
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia in the elderly: clinico-biological features, outcomes, and proposal of a prognostic model

Abstract: ABSTRACTnosis was estimated by calculation of the creatinine clearance using the Modification of Diet in Renal Disease (MDRD) formula. For patients aged ≥70 years, the Cumulative Illness Rating Scale (CIRS) was retrospectively assessed at the time of diagnosis (CIRS-D) and first-line treatment (CIRS-T).12,13 The assessment of the CIRS is detailed in the Online Supplementary Appendix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 37 publications
1
55
1
Order By: Relevance
“…Indeed, relevant comorbidities may shorten life expectancy and may reduce treatment tolerance, 3,17 and modern treatment algorithms recommended evaluating not only age, clinical staging, and disease-specific prognostic biomarkers, but also comorbidities to guide clinical decisions, 13,18 particularly in the era of novel drugs. 19 However, the prognostic impact of comorbidities and of the CK in the era of mechanism-based treatment needs to be specifically addressed in larger series of patients treated for longer periods of time because in our cohort of CLL, these agents were offered only in more recent years.…”
mentioning
confidence: 99%
“…Indeed, relevant comorbidities may shorten life expectancy and may reduce treatment tolerance, 3,17 and modern treatment algorithms recommended evaluating not only age, clinical staging, and disease-specific prognostic biomarkers, but also comorbidities to guide clinical decisions, 13,18 particularly in the era of novel drugs. 19 However, the prognostic impact of comorbidities and of the CK in the era of mechanism-based treatment needs to be specifically addressed in larger series of patients treated for longer periods of time because in our cohort of CLL, these agents were offered only in more recent years.…”
mentioning
confidence: 99%
“…In one study, the poor outcome of patients with comorbidities was due to a combined increase of treatment-related, CLL-unrelated and CLL-related mortality, thus suggesting complex interactions between the haematological disease, its treatment and comorbidities [11]. In another study, the outcome of patients with comorbidities was poor because of a sole increase in CLLunrelated mortality but not in CLL-related mortality [17].…”
Section: Impact Of Comorbidity On Outcomes In Patients With Cllmentioning
confidence: 96%
“…Commonly detected comorbidities in this study were hypertension (55 %), hyperlipidaemia (37 %), coronary artery disease (24 %), atrial fibrillation (21 %), diabetes mellitus (22 %) and osteoarthritis (22 %). In a cohort of 949 patients diagnosed with CLL in a haematology department of a university hospital, the median total CIRS score at the time of diagnosis was 5 [17]. A single-centre study of 133 untreated subjects found that 53 % of the patients had a total CIRS score of 6 or higher [18], while in a single-centre study of 143 untreated patients, fewer than 20 % had a total CIRS score above 6 [19].…”
Section: Prevalence Of Comorbidity In Patients With Cllmentioning
confidence: 99%
“…Clinical trials evaluating immediate chemo(immuno)therapy in early stage CLL so far failed to show an overall survival (OS) benefit; thus, watch and wait has remained the standard of care. 4,5 However, today novel treatment approaches are available (see below), and a wealth of prognostic factors have been identified, including lymphocyte doubling time (LDT), bone marrow infiltration pattern, serum thymidine kinase (TK) and ␤2-microglobulin (␤2-MG) levels, genomic aberrations assessed by fluorescence in situ hybridization (FISH), ZAP70, CD38, and CD49d expression, as well as the mutational status and structure of the immunoglobulin heavy-chain variable genes (IGHV) and gene mutations, most prominently TP53 (for overviews, see Stilgenbauer and Zenz 6 and Baumann et al 7 ). Numerous single markers and various models, scores, or nomograms have been reported to be associated with prognosis in early stage CLL, but there is a lack of prospective validation within clinical trials ( [8][9][10][11][12][13][14] ).…”
Section: Standard Approach To Early Stage Asymptomatic Patientsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] 72 This system clearly holds great promise to refine risk stratification based on staging and single parameters alone. However, it is derived from trials based on chemo(immuno)-therapy and may be challenged by the advent of the novel agents that may in themselves require the development of integrated risk scores highlighting the "moving target" nature of the prognostic/ predictive factor topic.…”
Section: Mrd Evaluationmentioning
confidence: 99%